Producción de un nanocompuesto con propiedades fotocatalíticas y magnéticas empleando Psidium guajava para la decolorar agua contaminada con azul de metileno y rodamina B (2024)
Industrial effluents, particularly those from the textile sector, are polluting water bodies with dyeing agents, posing a significant environmental threat. The need to remediate these waters is urgent, especially in the face of possible shortages. Conventional methods were not designed to eliminate this contaminant and can even generate secondary contamination.